(untitled) (Journal of NELTA, 2023)
A classroom is not only a place for female learners’ learning and growth but also a place for enacting their knowledge, power, positioning, and resistance in their classroom interaction. As important social members, these learners bring the society-approved discourses that restrict their gendered roles in their classroom participation. Female learners, dominated by their social-historical-cognitive selves, mostly do not try to initiate a conversation or participate in that as they have to contest the status quo of male learners who particularly dominate the conversation process. Hence, they have to struggle to negotiate their position and identity by resisting the ‘boy discourses’ that delimit their equal participation. This study focuses on the reproduction of resistance and the struggle for achieving the equality dynamics of the female learners to participate in classroom discourses. Six female learners and two teachers were the research participants at a private university in Chattogram, Bangladesh. Kumaravadivelue’s (1999) critical classroom discourse analysis (CCDA), van Dijk’s (2003; 2016) socio-cognitive and Wodak’s (2009) historical-cognitive model and Braun and Clerk’s (2006) thematic analysis approach had been used here as an analytical framework and for data analysis tool. Structured focus group interviews and classroom observation were the tools used for generating data that gave the impression that female learners use both active and passive resistance that happens due to the existing micro and macro factors surrounding them. Moreover, their historical, social, and cognitive positioning and struggle for negotiating power and identity gave them the insight that the classroom served both as a learning and growing space for them. This study contributes to the budding research on female learners’ being and becoming an identity in a powerful classroom interaction that can infl uence them beyond the classroom.